Click, Read, Buy: The Power of Online Reviews in Shaping Electronic Gadget Purchases on Shopee - Kia Hui Gan; Xiao Toing Hoo; Shin Heng; MengTing Hong; Xuan Wei Hoo; Srivastava Shivi; Daisy Mui Hung Kee (AIBPM Publisher, 2026)
In the contemporary e-commerce environment, online reviews represent a vital form of electronic word-of-mouth (eWOM) that influences consumers’ purchasing behavior, particularly in competitive marketplaces such as Shopee. Grounded in the Theory of Reasoned Action (TRA) and social proof theory, this study examines how review valence, review volume, and review quality influence consumers’ purchase intentions. Using a quantitative approach, survey data were collected from 205 Shopee users through Google Forms. The findings reveal that review quality the greatest influence on purchase intention, while review valence also contributes positively, albeit to a lesser extent. However, review volume does not significantly influence purchase intention. These findings highlight that detailed, credible, and high-quality reviews play a more critical role than the number of reviews in shaping consumer behavior. This study offers practical insights for sellers and marketers seeking to optimize review strategies and strengthen consumer trust on e-commerce platforms.